Ribavirin Inhibits Parrot Bornavirus 4 Replication in Cell Culture. - Jeffrey M B Musser; J Jill Heatley; Anastasia V Koinis; Paulette F Suchodolski; Jianhua Guo; Paulina Escandon; Ian R Tizard (PLoS ONE, 2015)
Parrot bornavirus 4 is an etiological agent of proventricular dilatation disease, a fatal neurologic and gastrointestinal disease of psittacines and other birds. We tested the ability of ribavirin, an antiviral nucleoside analog with antiviral activity against a range of RNA and DNA viruses, to inhibit parrot bornavirus 4 replication in duck embryonic fibroblast cells. Two analytical methods that evaluate different products of viral replication, indirect immunocytochemistry for viral specific nucleoprotein and qRT-PCR for viral specific phosphoprotein gene mRNA, were used. Ribavirin at concentrations between 2.5 and 25 μg/mL inhibited parrot bornavirus 4 replication, decreasing viral mRNA and viral protein load, in infected duck embryonic fibroblast cells. The addition of guanosine diminished the antiviral activity of ribavirin suggesting that one possible mechanism of action against parrot bornavirus 4 may likely be through inosine monophosphate dehydrogenase inhibition. This study demonstrates parrot bornavirus 4 susceptibility to ribavirin in cell culture.